As realizações de /R/ rm coda silábica na comunidade de Porto da Rua, litoral norte de Alagoas : análise lingüística e sociolinguística - Santos, Jeylla Salomé Barbosa dos (2010)
In the light of the Theory of Variation and Change and Generative Phonology, in this study, aims to investigate the performance of a segment /R/ in the community of Porto da Rua (in the northern coast of Alagoas). The phonetic environment in which this realization occurs was determined, as well as the influence of extralinguistic factors analysed. The corpus for this research consisted of 48 informants among men and women born in the community. The categorization of data and statistical analysis were done using the package VARBRUL. Data were coded according to linguistic and social groups of factors (GF). The results indicated that the variant under study may be undergoing a process of linguistic change, since those responsible for spreading the informants are not in school and age over 50 years. Data collection was done through recordings with spontaneous narratives. The objective is thus to study the correlation between linguistic phenomena and stratified external variables (gender, age and education).